PENGGUNAAN MODEL AIDA SEBAGAI STRUKTUR KOMUNIKASI PADA MEDIA SOSIAL INSTAGRAM - Brian Alvin Hananto (Jurnal Nawala Visual, 2019)
AIDA is a model that explains the steps or levels of consumer perception. Seeing how AIDA is often used as a basis for creating marketing strategies, the author would like to see whether AIDA could be used as a structure for visual communication strategy. The research was done by observing the design process of students from Universitas Pelita Harapan’s Visual Communication Design department. The author had asked the students to design their Instagram’s communication media using the AIDA model as their basis. By using narratology as their design approach, the designers divide timelines and the needs of communication to acts, plots and also Instagram panels. From the design that was done, the author concludes that the usage of structure to create a visual communication strategy helps to define what message is to be made and when should the message be posted on Instagram. The author hoped that this paper had shown the possibility of using AIDA as a communication structure, especially for social media.